Complexity, post-coloniality, transculturality : the birth of Wole Soyinka's Yoruba tragedy in Nigeria and its intercultural presentation in Britain - Adigun, Olabisi M. (Trinity College (Dublin, Ireland). Department of Drama, 2013)
In 1986, Wole Soyinka made history when he became the first African ever to win the Nobel Prize for Literature. Soyinka is a Yoruba man from western Nigeria and he began to write seriously and professionally in 1959 less than a year before Nigeria gained Its independerce from Britain in October 1960. Although Soyinka writes predominantly and masterfully in the English language, his plays and particularly his Yoruba tragedies are greatly influenced by ihe cultural paradigms of the Yoruba people of western Nigeria.
Keywords: Drama, Ph.D.; Ph.D. Trinity College Dublin